Ruthenium ion catalytic oxidation depolymerization of lignite under ultra-low dosage of RuCl3 catalyst and separation of the organic products with inorganic salts. Issue 7 (1st February 2023) - Wang, Qiufeng; Zhang, Yinling; Wang, Meng; Hao, Jianxiu; Le, Shukun; Liu, Quansheng; Li, Na; Zhou, Huacong
Abstract : We confirmed that reducing the use of a ruthenium catalyst can achieve a similar depolymerization efficiency only by extending the reaction time, and butanone extraction can achieve the separation of inorganic salts and organic components. Abstract : Depolymerization of lignite into valuable chemicals via ruthenium ion catalytic oxidation (RICO) is a potential route for the non-energy utilization of lignite. However, the high cost of the Ru catalyst during depolymerization and the high content of inorganic salts in the product solution limit the development of this route. In this work, RICO depolymerization of lignite was conducted under an ultra-low dosage of RuCl3 catalyst to decrease the usage of the catalyst during the RICO process. Different approaches were attempted to fulfill the separation of benzene polycarboxylic acids (BPCAs) products with the inorganic salts derived from the oxidant NaIO4, including butanone extraction and desalting via crystallization under different temperatures. The results show that lignite can be efficiently depolymerized under the mass ratio of RuCl3 /lignite as low as 1/1000 by prolonging the reaction time without decreasing the depolymerization degree and BPCAs yields compared to the commonly used mass ratio of 1/10. Butanone can extract ca. 91% of the total BPCAs in the product solution, and the inorganic salts content (mainly NaIO3 ) in the extraction solution was as low as 0.19 mg mL −1 . A new strategy of first acidification of depolymerization aqueous solution by HCl and then extraction by butanone is proved to be efficient for the separation of BPCAs with inorganic salts. Salting out via crystallization under lower temperature can remove ca . half content of the salts, and the efficiency is inferior to butanone extraction. The low usage of RuCl3 can efficiently decrease the catalyst cost of the RICO process, and butanone extraction can fulfill the enrichment of BPCAs and the separation of BPCAs with inorganic salts. This work is meaningful for the potential application of RCIO depolymerization of lignite for the production of valuable chemicals.